Positioning of the NOR-bearing chromosomes in relation to nucleoli in daughter cells after mitosis - Kalmárová, M; Smirnov, E; Kováčik, L; Popov, A; Raska, I (Physiological research, 2008)
It is known that chromosomes occupy non-random positions in the cell nucleus. However, it is not clear to what extent their nuclear positions, together with their neighborhood, are conserved in daughter cells. To address specific aspects of this problem, we used the model of the chromosomes carrying ribosomal genes that are organized in clusters termed Nucleolus Organizer Regions (NORs). We compared the association of chosen NOR-bearing chromosomes (NOR-chromosomes) with nucleoli, as well as the numbers of nucleoli, in the pairs of daughter cells, and established how frequently the daughter cells had equal numbers of the homologs of certain NOR-chromosomes associated with individual nucleoli. The daughter cells typically had different numbers of nucleoli. At the same time, using immuno-FISH with probes for chromosomes 14 and 15 in HeLa cells, we found that the cell pairs with identical combinations appeared significantly more frequently than predicted by the random model. Thus, although the total number of chromosomes associated with nucleoli is variable, our data indicate that the position of the NOR-bearing chromosomes in relation to nucleoli is partly conserved through mitosis.
Keywords: lidské chromozomy, pár 15; hybridizace in situ fluorescenční; Cell Nucleolus; Mitosis; Nucleolus Organizer Region; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 15; Models, Genetic; Chromosome Positioning; HeLa buňky; lidské chromozomy, pár 14; umístění chromozomů; lidé; HeLa Cells; organizátor jadérka; Humans; modely genetické; In Situ Hybridization, Fluorescence; mitóza; buněčné jadérko